Preparation of high purity silica originated from rice husks by chemically removing metallic impurities - Lee, Jin Hyung; Kwon, Jeong Heo; Lee, Jae-Won; Lee, Hye-sun; Chang, Jeong Ho; Sang, Byoung-In (Journal of industrial and engineering chemistry (Seoul, Korea), 2017)
[Display omitted] •A comparative study was carried out to synthesize silica particles from rice husk by using four chemicals.•Sulfuric acid and 1-butyl-3-methylimidazolium hydrogen sulfate were effective to remove metallic impurities.•The chemical treatments used in this study did not change the surface properties of silica.•The use of 1-butyl-3-methylimidazolium hydrogen sulfate improved both the productivity and surface area of silica. Chemical treatments were used to synthesize high-purity silica from rice husk. A comparative study was carried out by using four chemicals: sulfuric acid, hydrogen chloride, oxalic acid, and ionic liquid (1-butyl-3-methylimidazolium hydrogen sulfate). The ash content significantly increased in sulfuric-acid and the ionic liquid treatments with the removal of both cellulose and hemicellulose. Drastic increases of silica purity were observed in samples treated with sulfuric acid and the ionic liquid at 99.6% and 99.5%, respectively. Furthermore, the ionic liquid treatment increased the surface area and pore volume by 1.9 times and 2.4 times, respectively, with respect to the sample not subjected to chemical treatment.